Adiponectin, Leptin and Cardiovascular Disorders - Zhao, Shangang (Circ Res, 2021)
The landmark discoveries of leptin and adiponectin firmly established adipose tissue as a sophisticated and highly active endocrine organ, opening a new era of investigating adipose-mediated tissue crosstalk. Both obesity-associated hyperleptinemia and hypoadiponectinemia are important biomarkers to predict cardiovascular outcomes, suggesting a crucial role for adiponectin and leptin in obesity-associated cardiovascular disorders. Normal physiological levels of adiponectin and leptin are indeed essential to maintain proper cardiovascular function. Insufficient adiponectin and leptin signaling results in cardiovascular disorders. However, a paradox of high levels of both leptin and adiponectin is emerging in the pathogenesis of cardiovascular disorders. Here, we (i) summarize the recent progress in the field of adiponectin and leptin and its association with cardiovascular disorders, (ii) further discuss the underlying mechanisms for this new paradox of leptin and adiponectin action, and (iii) explore the possible application of “partial leptin reduction”, in addition to increasing the adiponectin/leptin ratio as a means to prevent or reverse cardiovascular disorders.